2006
DOI: 10.1097/01.mrr.0000210046.02044.4d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternative communication on the communicative effectiveness of an individual with a progressive language disorder

Abstract: This study was designed to investigate the effects of two different modes of communication on the communicative output of an individual who is no longer able to communicate verbally, presenting with a primary progressive aphasia and apraxia of speech. The two treatment approaches included training the patient with a text-to-speech alternative communication device and with American sign language. An alternating treatment design was used to compare two communicative approaches (an alternative communication devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 7 publications
0
21
0
2
Order By: Relevance
“…An evaluation by a speech therapist is useful for exploring alternative communication strategies [41]. …”
Section: Treatment and Therapeutic Strategiesmentioning
confidence: 99%
“…An evaluation by a speech therapist is useful for exploring alternative communication strategies [41]. …”
Section: Treatment and Therapeutic Strategiesmentioning
confidence: 99%
“…Pattee et al [40] compared a text-to-speech AAC device to sign language for a person with primary progressive aphasia and apraxia of speech. They reported that there was a greater increase in correctly used words using sign language, and the participant rated the device as less useful and less easy to use than sign language.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative communication devices, speech therapy, and American Sign Language may help some patients [39]. A summary of therapeutic recommendations was recently published [40].…”
Section: Treatment and Therapeutic Strategiesmentioning
confidence: 99%